Identitas Visual Milenial Dalam Merek Minuman Bubble Tea di Tangerang Selatan - Arief Ruslan (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2020)
This article investigates the visual identity of “newest” soft drink businesses that target milennial communities in the South Tangerang region. The “kekinian” drinks, popular as millennial drinks and make this business blooming and compete with one another. Appending from some form of visual identity from within